Sensitivity, specificity, positive predictive value and negative predictive value of selected clinical signs and symptoms associated with schistosomiasis japonica infection - Zhang Junhua
Several demographic variables, behavioral factors and selected clinical signs and symptoms thought to be associated with Schistosoma japonicum infection were evaluated regarding their ability to discriminate infected from non-infected individuals in a highly endemic area in China. This is preliminary to developing a simple screening tool for Schistoxoma japonicum infection. Occurrence of signs and symptoms of schistosomiasis among populations of a junior middle school and Quijia village of the Nanji township was elicited by interview using a structured questionnaire. Physical examinations were done to detect presence of hepatomegaly and splenomegaly. Infection status was determined by the presence of schistosome ova in the stools using the Kato-Katz thick smear method.Through multiple logistic regression analysis, it was found that sex, water contact, itchiness, and blood in the stools were significantly associated with Schistosoma japonicum infection. Females had a lower probability of infection than males. The longer the water contact (11-15 days) the higher the probability of infection compared with 0-5 days of water contact. The person with a history of itchiness in the past 15 days had higher probability of infection compared with those without itchiness. The person having blood in the stools had much higher probability of infection than those without blood in the stools.The sensitivity, specificity, positive predictive and negative predictive values of the signs and symptoms identifying Schistosoma japonicum were analyzed using the Kato-Katz technique as the gold standard. The sensitivities of the selected clinical signs and symptoms like diarrhea, fever, itchiness, abdominal pain, hepatomegaly below costal region, headache, malaise, watery stools, mucoid stools and bloody stools were only between 6.25and 50.89. Hepatomegaly below xiphoid process had the highest sensitivity (98.21), splenomegaly had the lowest sensitivity (4.46). "Blood in the stools" showed the highest specificity 999.47) and positive predictive value (94.44). Even when these parameters were calculated according to the combinations of signs and symptoms by sex and age groups, the sensitivity and specificity were still not desirable.The unit cost of Kato-Katz thick smear stool examination and interview were US$1.1 per slide and US$ per subject, respectively.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Schistosomiasis; Schistosoma japonicum